Analisis Pengaruh Faktor- Faktor Pendorong Tindak Kecurangan terhadap Kecendrungan Aparatur Pemerintah Melakukan Fraud (Persepsi Pegawai Dinas Kabupaten Banyumas) - Kholida Atiyatul Maula (Accounthink, 2017)
This study uses primary data through surveys and distribute quisoner to 30 respondents consisting of heads of sections and sub-sections DPPKAD, SETDA and BAPPEDA in Banyumas, to perform hypothesis testing methods quantitative descriptive survey. This study analyzed using multiple regression analysis. With the object of perception research include local government officials about income satisfaction, unethical behavior, effectiveness of internal controls, and the tendency to commit fraud. Based on the results of research and analysis using multiple regression analysis showed that partially or simultaneously variable income satisfaction, unethical behavior and the effectiveness of internal control (significant) against the tendency of government officials commit accounting fraud. The implication of this research is The effectiveness of internal control that the better it will reduce the tendency to commit fraud solution of this problem is in every line of the organization both sectors government and the private sector by modifying its internal control system that separates the task of recording of transactions that must be transparent and clear and penerepan authority and responsibilities maximum to reduce the chances of fraud, unethical behavior management is getting better is not necessarily reduce the tendency to commit fraud solution of this problem is the prevalence of the organization should be appropriate, independent in financial reporting, transparency of income beyond the basic salary, and improved performance manajemen.Kepuasan increasing income will reduce the tendency to commit fraud, the solution of the problem is with the level of salary (pay level) should correspond employees, salary increases (pay raise) to be adapted to the level of employment or class of employees.